Novel approaches for determination of antiretroviral reverse transcriptase inhibitor agent in commercial dosage forms by using spectrofluorimetric, first derivative spectrophotometric, and HPLC methods - Gizem Tiris; Emine Çiloğlu; Nevin Erk (SpringerOpen, 2020)
Abstract Background Rapid, simple, and sensitive spectrofluorimetric, first derivative spectrophotometric, and high-performance liquid chromatographic (HPLC) methods have been developed and validated for determination of tenofovir in pharmaceutical preparations. Spectrofluorimetric method is based on measuring the native fluorescence intensity of tenofovir at 375.0 nm after excitation at 275.0 nm. Calibration graphics were plotted and were found linear over 4.72-15.75 μg/mL concentration range (r 2 = 0.9994). The second method developed was the first derivative spectrophotometric method for the analysis of tenofovir performed by measuring the amplitude at 251.7 and 272.6 nm. Linearity was observed in the concentration range 10.0-28.0 μg/mL (r 2 = 0.9998). On the other hand, HPLC with a diode array detector (DAD). Ritonavir was used as internal standard (IS). HPLC analysis was carried out on a C18 column (Wakosil-II 5 C18 AR, 4.6 × 250 mm) using a mobile phase consisting of acetonitrile: 0.5% formic acid (99.5:0.5; v/v) at a flow rate of 1.0 mL/min. Injection volume was 5.0 μL. DAD signals at 260.0 nm were used. HPLC method was found to be linear over the concentration range of 10.0-100.0 μg/mL (r 2 = 0.9990). Result Intra- and inter-day analysis and recovery studies were carried out to investigate precision and accuracy of the proposed spectrofluorimetric, first derivative spectrophotometry and HPLC methods. Conclusion We successfully applied the developed methods for determination of tenofovir in tablet formulation. Finally, the proposed methods were compared statistically.